Analisis Motion Trajectory dan Fatigue Damage Ratio FPSO Terhadap Catenary Mooring Line Failure - Muhammad Alkhan Dwiki Abadi; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Floating Production Storage and Offloading (FPSO) is a ship that produces floating oil and gas by having a catenary mooring type mooring system. The FPSO will produce oil and gas in the Abadi Field in the Masela Block of the Arafuru Sea (09˚ 07' 51'' S / 130˚ 28' 00'' E) where the area has sea waves, wind and currents which will affect performance FPSO ship. In this research, Response Amplitude Operator (RAO), motion trajectory and fatigue damage ratio will be tested with a ship mooring system of 12 ropes, 3 of which experienced failure. The conclusion of this research is that the more mooring ropes break, the farther the FPSO ship will move from its initial condition and the higher the maximum rope tension value, it will be directly proportional to the stress range on each mooring rope, while for the fatigue damage ratio, the higher the failure cycle value. then it will be inversely proportional to the fatigue damage ratio value for each mooring rope.